Victorian Gothic and Art Deco ensembles of Mumbai - Ghosh, Ayan (Jio Institute, 2023)
Victorian Gothic and Art Deco Ensembles of Mumbai were recognized by UNESCO as World Heritage sites in 2018. The Art Deco buildings lie along Maharshi Karve Marg, and they face the Victorian Gothic buildings across the Oval Maidan, which consist of the Public Works Department, Bombay High Court and University Library & Convocation Hall.